Strengthening the Role of Family Businesses in the Czech Republic : A Proposal for Government Action - Šenkeřík, Jan; Jurek, Martin; Kubíček, Aleš; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
Family businesses are a crucial part of economies worldwide; therefore, this paper looks at how the Czech government can provide better support for Czech family businesses to help them become a strong and stable cornerstone of the economy. To identify the improvement of family business supporting practices, an analysis of the current status of the Czech Republic and multiple other countries worldwide was conducted with surveys of Czech and international consumers and interviews with Czech family businesses. The findings showed that the Czech Republic compares well to other countries with only minor suggestions like lowering of inheritance tax, but the interviews showed the disgust of interviewed firms toward the financial support and constant interference with their businesses. Lastly, surveys suggested that differentiation would be found beneficial by the consumers. In conclusion, less interference with business and more light support of a well-marketed Czech family business logo for easier differentiation or tax incentives for generational introduction to the business can provide the needed assistance that family businesses would appreciate from the government.
Vedoucí práce: Martin Jurek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses